2016
DOI: 10.1167/iovs.15-18272
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Kallikrein Mediates Vascular Endothelial Growth Factor–Induced Retinal Dysfunction and Thickening

Abstract: PurposePlasma kallikrein is a serine protease and circulating component of inflammation, which exerts clinically significant effects on vasogenic edema. This study examines the role of plasma kallikrein in VEGF-induced retinal edema.MethodsIntravitreal injections of VEGF and saline vehicle were performed in plasma prekallikrein–deficient (KLKB1−/−) and wild-type (WT) mice, and in both rats and mice receiving a selective plasma kallikrein inhibitor, VA999272. Retinal vascular permeability (RVP) and retinal thic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…The cellular distribution of B 1 receptors also overlapped VEGF‐R2 in the retina in the CNV model. Whereas B 1 receptors and VEGF may interact in the retina (Clermont et al, ; Kita et al, ), only three studies have explored the role of the KKS in AMD aetiology. The first showed that the KKS was a positive regulator of CNV through the additive effects of a B 2 receptor antagonist and ACE inhibition on the reduction of CNV (Nagai et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The cellular distribution of B 1 receptors also overlapped VEGF‐R2 in the retina in the CNV model. Whereas B 1 receptors and VEGF may interact in the retina (Clermont et al, ; Kita et al, ), only three studies have explored the role of the KKS in AMD aetiology. The first showed that the KKS was a positive regulator of CNV through the additive effects of a B 2 receptor antagonist and ACE inhibition on the reduction of CNV (Nagai et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The co‐localization of VEGF‐R2 and B 1 receptors on retinal blood vessels is congruent with the possibility that VEGF acts partly through the KKS system. Both VEGF and B 1 receptors caused breakdown of the blood‐retinal barrier in numerous ocular diseases, including neovascular AMD (Clermont et al, ; Gragoudas et al, ; Qaum et al, ; Saishin et al, ). A single anti‐VEGF IVT injection reduced the formation of vascular damage in retina and prevented the increase in retinal vascular permeability in laser‐induced CNV, concomitant with a down‐regulation of B 1 and B 2 receptors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, intravitreal injection can be used to distinguish between the treated and untreated eye of a mouse [62-66]. Furthermore, using curcumin in utero might inhibit degeneration entirely [28], given that it might be a better way to use curcumin prenatally for those who at high risk for RP.…”
Section: Discussionmentioning
confidence: 99%